Evaporative Cooling: A Review of its Types and Modeling - Hashim, Rasha Hayder; Hammdi, Salman Hashim; Eidan, Adel Abid Alaziz (Basrah Journal for Engineering Sciences, 2022)
Evaporative cooling is a widely used energy-saving and environmentally friendly cooling technology. Evaporative cooling can be defined as a mass and heat transfer process in which the air is cooled by the evaporation of water and as a result a large amount of heat is transferred from the air to the water and thus the air temperature decreases. Evaporative cooling is mainly used in many cooling technologies used in buildings, factories, agricultural in addition to it is used industrially in cooling towers, evaporative condensers, humidification, and humidity control applications. Evaporative cooling is divided into direct evaporative cooling and indirect evaporative cooling, as well as water evaporative cooling and air evaporative cooling. This paper reviews the most important developments and technologies in evaporative cooling that lead to lower energy consumption and provide suitable cooling comfort.